Psychological skill training to improve golfer`s performance - Park, J.-K.; Yoo, S.-l.; Lim, S.-J. (International Journal of Coaching Science, 2021)
The purpose of this study was to investigate the psychological skill training to improve golfer's performance. Twenty-five elite golfers (17 men and 8 women) paiticipated in the study. 20 professional golfers (12 men, 8 women) and 5 national players (5 men) were selected to participate in the study. In this study, 64 closed and open questions were used to identify the stressors and coping strategies of golfers. There are countless stressors affecting golf performance. Among them, the four factors that have been identified as the most influential factors for the players were explained, natnely, the error of club-choice, decreased concentration, anxiety, and physical condition. And also the sources of stress and coping strategies in each part were explained. Finally, psychological counseling techniques for improving golf performance were shown as practice, effort, goal setting, attention, positive thoughts, confidence, motivation, forgetting, psyching-up, mind control, and image training.